Chapter Nicholas Trevet : le théologien anglais qui parlait à l'oreille des Italiens - Dufal, Blaise (Reti Medievali E-Book, 2020)
The commentaries composed by the English theologian Nicholas Trevet at the beginning of the fourteenth century not only bear witness to his connections with Santa Maria Novella. They also testify to the importance of his contribution to the transfer of knowledge about Antiquity and the rebirth of antiquarianism in the Italian peninsula. This essay argues that Trevet's Scholastic commentaries, presented as an expositio, met the need that Italian intellectuals had of a fuller understanding of classic literature, pagan mythology and Roman history.